The importance of food for children in the first two years of life (Research, Society and Development, 2022)
Introduction: The early introduction of inadequate complementary feeding can lead to the occurrence of diseases and infant morbidity and mortality, with the chance of increasing early weaning. This study aims to raise awareness among parents about the importance of breastfeeding and healthy eating, providing greater knowledge and healthy practices. Methodology: This is a bibliographic review, sites such as SciELO (Scientific electronic library online), Pubmed (National Library of Medicine), government sectors such as MS (Ministry of Health), WHO (World Health Organization, scientific journals and books) were used. To search for articles, the following descriptors were used: complementary feeding; eating habits; breastfeeding; food consumption; micronutrients. Result and discussions: the study shows the importance of a healthy diet during the first years of life, as it contributes to child development, in addition to preventing the occurrence of diseases such as obesity and anemia during childhood. It was also possible to observe the influence of parents on the eating habits of children in the age group of the study, so it is important that there are public policies for nutritional education as a way of informing parents about healthy eating.